Antibodies in lymphocyte supernatants can distinguish between neutralising antibodies induced by RSV vaccination and pre-existing antibodies induced by natural infection - Gerretsen, H; Capone, S; Vitelli, A; Reyes, L; Thompson, A; Jones, C; Green, C; Pollard, A; Sande, C (Elsevier, 2018)
Introduction Respiratory syncytial virus (RSV) is the single most important cause of severe respiratory illness in infants. There is no effective vaccine and the only effective treatment available is the monoclonal antibody palivizumab which reduces the risk of severe RSV disease in prematurely born infants. However, palivizumab is too costly to allow for wide implementation and thus treatment is restricted to supportive care. Despite extensive efforts to develop a vaccine, progress has been hindered by the difficulty in measuring and assessing immunological correlates of RSV vaccine efficacy in the presence of high levels of pre-existing RSV antibodies. Methods Here we describe a new method for measuring the functional activity of antibodies induced by vaccination distinct from pre-existing antibodies. Antibodies in lymphocyte supernatants (ALS) from the cultured peripheral blood mononuclear cells (PBMCs) of young adults who had recently been vaccinated with a novel RSV candidate vaccine were directly assayed for virus neutralising activity. An ELISA method was used to measure antibodies in nasal and serum samples and then compared with the adapted ALS based method. Results There was a wide background distribution of RSV-specific antibodies in serum and nasal samples that obscured vaccine-specific responses measured two weeks after vaccination. No RSV-specific antibodies were observed at baseline in ALS samples, but a clear vaccine-specific antibody response was observed in ALS seven days after the administration of each dose of vaccine. These vaccine-specific antibodies in ALS displayed functional activity in vitro, and quantification of this functional activity was unperturbed by pre-existing antibodies from natural exposure. The results demonstrate a promising new approach for assessing functional immune responses attributed to RSV vaccines.